2000
DOI: 10.1007/pl00007536
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D3 receptor variant and tardive dyskinesia

Abstract: In the search for genetic factors contributing to tardive dyskinesia, dopamine receptor genes are considered major candidates. The dopamine D3 receptor is of primary interest as dopamine D3 receptor knock-out mice show locomotor hyperactivation resembling extrapyramidal side-effects of neuroleptic treatment. Furthermore, Steen and colleagues (1997) recently reported an association between tardive dyskinesia and a dopamine D3 receptor gene variant. In the present study we tried to replicate this finding. We inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
40
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 19 publications
4
40
2
Order By: Relevance
“…This was not true of DRD3 which, intriguingly, was found to be associated with TD by our group 4 and by Basile et al 5 and is a widely although not universally replicated genetic association with TD. [9][10][11] On the other hand, there was a significant age effect of HTR2A for which there was a disparity between our findings 2 and those of Basile et al 3 As noted, the sample examined by Basile et al 3 was two decades younger, on average, than our sample. There is considerable evidence from post-mortem and neuroimaging studies that brain serotonin receptor density, particularly 5-HT2A receptor density, is reduced with age (reviewed in Cidis Meltzer et al 12 ).…”
Section: Agecontrasting
confidence: 70%
“…This was not true of DRD3 which, intriguingly, was found to be associated with TD by our group 4 and by Basile et al 5 and is a widely although not universally replicated genetic association with TD. [9][10][11] On the other hand, there was a significant age effect of HTR2A for which there was a disparity between our findings 2 and those of Basile et al 3 As noted, the sample examined by Basile et al 3 was two decades younger, on average, than our sample. There is considerable evidence from post-mortem and neuroimaging studies that brain serotonin receptor density, particularly 5-HT2A receptor density, is reduced with age (reviewed in Cidis Meltzer et al 12 ).…”
Section: Agecontrasting
confidence: 70%
“…Recently, a genotypic association between the DRD3 receptor polymorphism and a susceptibility to neuroleptic-induced motor disturbances such as tardive dyskinesia and akathisia in schizophrenic patients was obtained in a number of studies [9][10][11][12] except for one. 13 Furthermore, the association between the DRD3 polymorphism and a schizoaffective variant of schizophrenia was reported. 14 The identification of vulnerability genes for schizophrenia is compounded by the wide range of phenotypic variability postulated in this illness and it has recently been suggested that in genetic studies some clinical or biochemical markers should be used to diminish this variability.…”
mentioning
confidence: 99%
“…In order to shed light on these controversial results, recently, Lerer et al 6 performed a combined analysis including data from 780 patients from six research centers, dividing patients into eight groups based on their population origin. Most of the data have been published previously either in peer reviewed journals [43][44][45][46][47] or in abstract form 48,49 (see Table 2 for more details). The authors applied stepwise logistic regression, and confounding effects of group, age and gender were taken into account.…”
Section: The Dopaminergic Systemmentioning
confidence: 99%